Justification for the Composition and Method of Active Pharmaceutical Ingredients Administration at the Development of Suppositories for the Treatment of Benign Prostate Gland Diseases - Masliy, Ju. S. (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: Diseases of the prostate gland occupy one of the main places in the structure of urological diseases and acquire ever increasing social significance. They are the most common diseases associated with aging in men. In conservative treatment of patients with diseases of the prostate gland, considering pathogenetic mechanisms, medicines of different directionalities are used, eliminating infectious agents, correcting the immune status, contributing to the regression of the inflammatory process and restoring the functional activity of the prostate. Materials and Methods: Indole-3-carbinol (Sigma-Aldrich Co., USA) and meloxicam (Boehringer Ingelheim GmbH, Germany) were chosen as the study objects. Studies of the active pharmaceutical ingredients (APIs) solubility were made, their crystallographic and thermogravimetric analyses. Results and Discussion: In the work, it has been substantiated the composition of rectal suppositories for the treatment of benign prostatic diseases using a combination of indole-3-carbinol and meloxicam, which possess anti-inflammatory, analgesic, and antibacterial properties and also contribute to the restoration of the hormonal background of men with age-related changes and activation of regeneration processes of the injured organ. AÂ microscopic and thermogravimetric analysis of selected APIs was carried out, and their solubility in aqueous and non-aqueous solvents was investigated. Conclusions: Based on research results, the optimal auxiliary substances were selected for rational introduction of substances into the suppository base â€“ polyethylene oxide-400, Tween-80. The results of thermogravimetric analysis have proven the thermostability of the investigated APIs in the temperature range the suppository bases melting.